Measurement and Application of Radium and Radon in the Environment - Guebuem Kim (Journal of Analytical Science and Technology, 2011)
The measurement of low-level Ra and Rn isotopes in water samples has become increasingly convenient and accurate in recent years. I summarize these new and advanced techniques and then introduce their application fields in geophysical and environmental studies.